KEANEKARAGAMAN JA BAMBU DI PULAU SUMBA - Kartini Kramadibrata (Research Center for Biology-Indonesian Institute of Sciences, 2011)
Arbuscular fungi (AF) associated with eight species of bamboo in Sumba island was studied. The study was initiated by collecting soil samples from bamboo rhizospheres followed by mass propagation of AF by culturing in pot. After several months soil from pot cultures were wet sieved and decanted followed by centrifugation and spores of AF were collected, identified by morphological characters under light microscope. The result showed that diversity of AF in bamboo in Sumba island is low but record of Acaulospora foveata on Bambusa blumeana, Dinochloa sp. and Nastus reholttumianus; A. scrobiculata on B. blumeana,Schizostachyum brachycladum (green) and N. reholttumianus; A. tuberculata on Gigantochloa attter, S. brachycladum (yellow) and S. lima; Glomus etunicatum on G. atter; and G. rubiforme on G. atter associated with bamboo is new for Indonesia.